Examining the Development of Banking Sector Regulations and Supervision Practices across BRICS and G7 Countries - Alam Ahmad; Asif Khan; Samreen Akhtar; Hafiz Wasim Akram (Complexity)
The study examines the development in the banking regulatory practices across BRICS nations over the period 2000–2019. The convergence and sustainability of the regulatory framework in BRICS nations to G7 norms have also been assessed. The analysis is based on five key regulatory measures, which include activity restrictions, entry requirements for a new bank, foreign bank entry restrictions, capital stringency, and deposit insurer powers. The study constructs the regulatory indexes based on the central bank responses to the Bank Regulation and Supervision Survey (BRSS) conducted by the World Bank. To estimate the indexes, the study follows Barth, Caprio, and Levine guidelines. The result reveals that the regulators of BRICS countries impose higher restrictions on bank activities than in the G7 nations. Furthermore, the United Kingdom and Brazilian bank regulators are more liberal and imposed fewer restrictions on insurance activity only. In addition, getting a bank license is tough in both regions. Regulators allow only fit and proper applicants into the banking domain. Furthermore, the authors find that the requirements for capital are becoming more restricted in BRICS nations between 2003 and 2019 to align with Basel capital accords, relative to G7 nations. The study documents a convergence in the banking licensing requirements, and limitations on foreign bank entry and official supervisory powers in the BRICS countries with the G7 nations. The study suggests that the regulators must offer freedom to banks’ activities with increasing supervision, and it boosts the competition in the banking sector and enhances customer welfare. Furthermore, the policymakers need to redesign the deposit insurance mechanism and equip deposit insurers with more powers to enhance the safety of depositors’ interests and minimize the moral hazards in the banking sector in both regions.